RETRACTED: The COVID-19 fear, anxiety, and resilience among emergency nurses - Karimi Khordeh, Negar; Dehvan, Fazel; Dalvand, Sahar; Repišti, Selman; Ghanei Gheshlagh, Reza (Frontiers in Psychology, 2022)
Abstract Background: In addition to physical complications, COVID-19 is associated with psychological issues such as fear and anxiety. High resilience in nurses enables them to adopt positive coping mechanisms and successfully operate in the stressful environment of COVID-19 wards. The present study aimed to evaluate the correlation between COVID-19 fear and anxiety with resilience in the emergency nurses of the hospital affiliated to Kurdistan University of Medical Sciences (west of Iran) in 2021. Methods: This cross-sectional study was conducted on 295 emergency nurses of selected hospitals in Kurdistan province, Iran in 2021. Data were collected using a demographic questionnaire, Fear of COVID-19 scale, Corona disease anxiety scale, and Connor-Davidson resilience scale. Data analysis was performed in R software version 3.6.3. Results: The mean scores of resilience, COVID-19 fear, and COVID-19 anxiety were 55.07±19.82, 20±7.37, and 36.48±13.21, respectively. A significant correlation was observed between COVID-19 fear and anxiety, which indicated that if the other demographic variables remained unchanged, a one-unit increase in the scores of COVID-19 fear and anxiety decreased the mean score of resilience by -0.66 (P=0.008) and -0.34 (P=0.015), respectively. Conclusion: COVID-19 fear and anxiety were significantly correlated. Therefore, providing training courses for promoting resilience could reduce the fear and anxiety of nurses during the COVID-19 pandemic.